PENDEKATAN KONSTRUKTIVIS SOSIAL DALAM PENINGKATAN HASIL BELAJAR IPS DI SD KELAS IV - Elsinora Mahananingtyas (PEDAGOGIKA: Jurnal Pedagogik dan Dinamika Pendidikan, 2018)
Learners at elementary school age generally have a concept that is rich, but not systematically, not organized and spontaneous. With a skilled supervisor dialogue together, then learners can develop the concepts that are more systematic, logical, and rational. A social constructivist approach stresses the social context in learning that knowledge is constructed and built together with the teacher or friend of the more skilled colleagues. The purpose of this research is to improve or enhance quality (quality) were learning in class by applying the social constructivist approach at grade IV in the primary Christian Advent of Ambon. The method of this research is a type of class action Research with 4 stages, namely planning, implementation, observation and reflection. The results of this research that is happening gradual classical on the learners of the cycle I meeting 1 to 2 meetings amounted to 6.6% of the cycle I of the meeting 1 of 59% to 65.6% in meeting 2. While the ketuntasan of classical learners on cycle II increased to 6.8% in cycle II meeting 1 of 77.2% to 84%. Cycle II whole learners, prepared with a value above the KKM i.e. 15 learners or 100% complete